PENDIDIKAN KARAKTER ANAK MELALUI TRADISI ANGON PUTU PADA MASYARAKAT DESA SOWAN LOR KEDUNG JEPARA - Fathur Rohman; Saputri, Nur Azizah (Irfani, 2025)
Tradition is one of the ways in which Javanese society conveys its norms and values. This is also true of the angon putu tradition, which is preserved by the community of Sowan Lor Kedung Jepara Village. This tradition holds many noble values that are worthy of development for character education, particularly for children. Therefore, this article aims to identify the meaning behind the angon putu tradition and the character education values for children embedded within it. This study is a descriptive-qualitative research. In data collection, the researcher used observation techniques by observing the implementation of the tradition, interviews with those involved, and documentation. The data analysis in this study used descriptive analysis techniques with the stages of reduction, display, and verification. The results of this study indicate that the angon putu tradition is a symbol of the love of grandparents for all their grandchildren and an expression of gratitude for the gift of long life. Meanwhile, the values that can be derived from this tradition include cooperation, independence, democracy, and social care.